Occupational Safety and Health Studies in Nepal - Joshi, SK; Shrestha, S; Vaidya, S (International Journal of Occupational Safety and Health, 2011)
Occupational safety and health are key issues today, with growing industrialization and labor market. To introduce and maintain a high standard of safety and health at workplace, it is essential to have an overall picture of the present workplace scenario, different hazards and probable health effects. This is a review of all previously published articles on occupational safety and health in Nepal. Key words such as Nepal, Occupation, Safety, and Health were used to search for relevant articles in PUBMED and Google Scholar. A total of 15 research articles were found, which dealt with different forms of work, like agriculture, health services, child labor, small scale household industries, brick kilns, and textile factories. The overall status of occupational safety and health does not look satisfactory. Standard work situations and criteria have to be set up and regular monitoring should be done to ensure the maintenance of quality at work. Key Words: environment; exposure; hazards; labor; work place DOI: http://dx.doi.org/10.3126/ijosh.v1i1.4725 International Journal of Occupational Safety and Health, Vol 1 (2011) 19-26